EFFECTS OF VEGETATION CHARACTERISTICS ON MICROCLIMATE CONDITION IN URBAN AREA - Mustamin Rahim (ICETIA, 2016)
The rise of temperature outdoor has a significant effect on temperature increase inside building, so that it becomes harder to achieve thermal comfort in summer and causes more utilization of air conditioner occurs. Trees should be considered as real means for the improvement of microclimatic conditions in outdoor spaces. Based on those conditions, this research investigates the effects of vegetation characteristics to the urban climate by literature review and simulation of meteorological model MM5. The results show that vegetation characteristics can influence the thermal performance and microclimate conditions. Evergreen broad leaf forest can reduce temperature of about 3°C and mixture vegetation and water bodies can reduce temperature by more than 5°C. Therefore, vegetation is useful to improve human environment in future.